Design Patterns for Visualization of User Activities in a Synchronous Shared Workspace - Nilsson, Stefan (International Journal of Advanced Corporate Learning (iJAC), 2015)
Scholars in fields such as Computer-Supported Collaborative Learning (CSCL) have extensively covered the general theme of distributed collaboration in the past few decades. Recent advances in web technologies have pushed forward the boundaries of what is possible to create on the web, aiding the development of various types of collaborative software. Standing on the shoulders of previous research, and in the light of the new web technologies, we here outline the development of what we label a “synchronous shared workspace”. The purpose of the system is to serve as a web-based collaboration tool for small groups of geographically and/or temporally dispersed persons within a learning context. Designing this type of system presents interesting challenges on how to graphically visualize the presence of others and their activities, i.e. awareness information. Further, the system provides other types of functionalities such as visualizing previous activities and real-time manipulation of media objects that provides challenges for designers. Utilizing a “design pattern” approach, this paper explores visualization patterns for collaboration in shared workspaces in order to support mutual awareness and coordination activities. Five design patterns were implemented in the system and evaluated by a small group of online learners. The results support the notion that visualization of awareness information is a complex issue and that the work to provide effortless coordination of collaboration is a research interest that needs more attention.